Monosialoganglioside GM1 reduces toxicity of Ptx and increase anti-metastasic effect in a murine mammary cancer model - Leonhard, Victoria (2020)
Having demonstrated the ability of monosialoganglioside GM1 micelles as oncology drug transporter, this work focuses on evaluating its application in an in vivo system, studying the toxicity and antitumoral effect of GM1-Ptx micellar formulation. The maximum tolerated dose (MTD) obtained after intravenous administration of GM1-Ptx in mice was 55 mg/kg and the 50% lethal dose (LD50) was 70 mg/kg. This value is higher than those described for the commercial formulations TAXOL and ABRAXANE, with LD50 of 30 and 45 mg/kg respectively. The antitumor activity, mortality and incidence of metastasis were studied on a murine model of mammary gland cancer. The GM1-Ptx formulation was administered i.v. at different doses for 9 weeks using empty GM1 micelles and saline as treatment controls. Once the treatments were completed, biochemical markers were quantified and histological tissue tests were performed. The most promising results were obtained with the treatment at a dose of 15 mg/kg/twice a week, condition in which a longer survival and significant reduction in the incidence of animals with metastasis, since only one 25% of the mice showed presence of pulmonary micro metastases.